Outcome of feminizing genital reconstruction in female sex assigned disorder of sex development in a low-income country. Issue 3 (May 2019) - Ekenze, S.O.; Chikani, U.N.; Ezomike, U.O.; Okafor, D.C.
Summary: Background: In patients with disorders of sex development (DSD), surgical/medical treatments are undertaken after sex assignment to ensure congruent bodily appearance and function. Genital reconstruction in these patients can be daunting with varied outcome. Understanding these outcomes is imperative, more especially in a developing country where added challenges exist. Objective: This study evaluates the outcome of genital surgery in patients with DSD assigned female sex. Methods: A retrospective analysis of 25 cases of female sex assigned DSD managed in two tertiary centers in southeast Nigeria was performed. Data of these cases were collected from the case notes, discharge summaries, and theater records. IBM SPSS Statistics Data Editor, version 21, was used for data entry and analysis. Results: The patients presented at median age of 12 months (range 2 days–30 years), with 15 (60%) cases reared as female and 10 (40%) reared as male before presentation. The predominant phenotype was phallus with empty fused/unfused labioscrotum and urethra opening in the labioscrotum or perineum in 21 (84%) patients. Evaluation revealed features suggestive of 46XX DSD in 21 (84%) patients, ovotesticular DSD in two (8%), and androgen insensitivity in two (8%). A total of 10 cases required sex reassignment after evaluation. Overall, 24 of the 25 cases had feminizing genital procedures. After a median follow-up period of 2 years (range 2 months–8 years), six (25%) cases developed procedure-related complications, three (12.5%) had social maladjustment, and two (8.3%) patients reported features of gender dysphoria. Discussion: The procedures of feminizing genitoplasty in this study did not differ from the established procedure. However, as a result of challenges of delayed presentation, inadequate early management, sociocultural factors, and a lack of facilities for full evaluation, some cases may require sex reassignment and more daunting reconstructive procedures. This may give rise to less than optimal outcome. The study was limited by the retrospective nature, small number of cases, and the short duration of follow-up of the cases. Conclusion: Feminizing genital procedures for DSD in our setting may be associated with procedure-related complications and non-surgical complications. Improving surgical technique and addressing the challenges of delayed presentation and fixation on male gender may improve overall outcome.The operative procedures and the outcome are summarized in the following table. Feminizing genital procedures and the outcome in the female sex assigned DSD patients Procedure n (%) Surgical complications Psychosocial sequelae Nil Surgical wound infection Vaginal stenosis *Social maladjustment Gender dysphoria Clitoroplasty and vulvoplasty 12 (48%) 12 0 0 0 0 Clitoroplasty, vulvoplasty, and prepubertal cutback vaginoplasty 5 (20%) 1 0 4 1 1 Clitoroplasty, vulvoplasty, and postpubertal cutback vaginoplasty 3 (12%) 0 0 0 2 1 Orchidectomy, clitoroplasty, labioscrotal reduction vulvoplasty, and colon substitution vaginoplasty 2 (8%) 1 1 0 0 0 Orchidectomy, clitoroplasty, labioscrotal reduction vulvoplasty, and awaiting colon substitution vaginoplasty 2 (8%) 1 1 0 0 0 No procedure (parents refused assigned gender) 1 (4%) – – – – – Total 25 15 2 4 3 2 ∗ CAIS, complete androgen insensitivity syndrome